Verso il caldo astratto. Una scampagnata geofilosofica. - Paolo Vignola (Kaiak, 2018)
This paper aims to describe a kind of thermal line within Deleuze's thought, which allows his concepts to be disseminated in tropical realities, as the same French thinker seems to announce in a passage of his Nietzsche and philosophy. The focus of the article is to show the plastic metamorphoses of Deleuze's key political concepts, such as "Image of thought", "Difference", "rhizome", "Fold", "nomadism", "geophilosophy", due to its strategic and post-colonial adoption by thinkers such as Eduardo Viveiros De Castro, Bolívar Echevería, Édouard Glissant. The sense of this ethno-philosophical journey is to highlight the geopolitical need for a reactivation capable of differentiating Deleuze's concepts, in order to avoid or at least counter-attack the European and Western self-referentiality in reading, interpreting and appliying the Deleuzian philosophy. The opportunity of such a theoretical description has been given by the personal experience of extremely humid heat that I did during a talk at the University of Roma 3, in which I presented a work entitled "Nietzsche in the Amazon. For a Nomadology beyond the Anthropocene and Accelerationism". Such personal experience, which I intend to describe in intensive terms, will function as a choreography (in a Derridian sense) for the theoretical themes of this work.